An Experimental Study of a Cyclonic Vertical Axis Wind Turbine for Domestic Scale Power Generation. (2015) - Loganathan, Bavin; Chowdhury, Harun; Mustary, Israt; Alam, Firoz
Abstract: The primary objective of this paper is to investigate a cyclonic domestic scale vertical axis wind turbine with semicircular shaped blades under a range of wind speeds. A 16-bladed rotor was initially designed and itstorques and angular speeds were measured over a range of wind speeds using a wind tunnel. Additionally, a cowling device was developed to enhance the turbine efficiency by directing the air flow from the rear blades into the atmosphere. Another 8-bladed rotor was also manufactured to investigate the effect of blade number on the maximum power generation. The aerodynamic performance of the cowling device wasalso investigated. Maximum power curves as a function of wind speeds were established for each configuration. The results indicated that the 16-bladed wind turbine can be used for domestic scale wind power generation. The results show that the cowling device has positive effect to increase the rotor speed to a significant amount. With the use of the cowling device, the average rotor speed increased by about 26% for the 16-bladed rotor compared to the baseline configuration. A significant increase (about 40%) of rotor speed was also found for the 8-bladed rotor with the cowling device. The results also indicated that the cowling device can be used to increase the power output of this cyclonic type vertical axis wind turbine especially with a reduce number of blades.